Determination of Oil and Garlic Chips Deterioration Rate during Vacuum Frying (Study on Engineering Aspect) - Yuniarto, Kurniawan; Sumarsono, Joko; Maryati, Sri; Alamsyah, Ahmad (Fakultas Teknologi Pertanian Universitas Brawijaya, 2010)
Garlic was fried continually with vacuum frying equipment using temperature 85C and ratio of garlic to oil of 1/10 (w/v) for 15 hours. Frying time was 75 minutes for each with final yield of garlic chips was 0.35, final moisture content of 4.2%, and final oil content of 32.6%. Physical and chemical characteristics for oil and garlic chip deterioration based on alysin content showed that the alysin content of garlic chips was 1.99-2.65 times fresh garlic with decrease constant was 0.04 hour-1. Free fatty acids formation was 0.0184% hour-1 with free fatty acids range 0.029-0.058%. It was below standard value of free fatty acid i.e. 0.5%. Peroxide value formation was -0.11mek kg-1 hour-1 with peroxide value ranged 9.5514-10.6642 meq kg-1. It was also below standard value of 50 meq kg-1. Carotene deterioration was 0.0184% hour-1 with its content ranged 0.029-0.058%, that still below standard value 0.5%. Fatty acids formation was 0.0184 % hour-1 with carotene range between 6.05-11.44% per 100 gram. Frying oil lightness value ranged 46.6-48.5, redness value ranged 16.7-18.8, and yellowness value ranged 20.0-24.6. Lightness decreased with decreasing rate constant of 0.036 hour-1, redness 0.013 hour-1, and yellowness 0.17 hour-1. Garlic chip lightness value ranged 56.0-58.1, redness value ranged 20.9-27.5. and yellowness value ranged 29.9-32.1. Lightness of garlic chip decreased with rate constant of 0.017x2 + 0.218x, redness of 0.023x2 - 0.331x, yellowness of -0.083x2 + 1.2x. Correlation between peroxide deterioration of oil to garlic chips was 0.65, correlation between free fatty acid deterioration of oil to garlic chip was -0.78, correlation between lightness of oil to garlic chip was -0.75, correlation between redness of oil to garlic chip was -0.89, and correlation between yellowness of oil to garlic chip was -0.68. This result showed that oil life cycle was 150 hours.Keywords: vacuum frying, garlic chip, deterioration rate, carotene, alysin, correlation